(untitled) (International Journal of Food and Nutritional Sciences, 2021)
This study investigates the thermal effects on the dielectric response of soil at varying moisture levels to enhance soil moisture estimation and remote sensing accuracy. Using a range of temperatures (0°C to 40°C) and moisture contents (5% to 30%), we measured the dielectric constant of sandy and clay soils. Results show a significant increase in the dielectric constant with higher moisture content, with sandy soils exhibiting values from 3.2 at 5% moisture to 18.6 at 30%, and clay soils ranging from 4.5 to 25.3. Temperature had a marked effect, reducing the dielectric constant from 29.5 to 19.8 in clay soil as temperature increased. These findings indicate that temperature corrections are essential for accurate soil moisture measurements. The study also compares the experimental results to theoretical models, revealing that existing models may underestimate temperature effects, especially in drier soils. The implications of these findings are significant for precision agriculture, environmental monitoring, and remote sensing, where accurate soil moisture data are critical. By integrating temperature effects into soil moisture models, this research provides a more accurate basis for resource management and environmental monitoring.